Analisis Hukum Ekonomi Syariah terhadap Praktik Fake Order (FO), Fake Buyer (FB), dan Fake Review (FR) dalam Perdagangan Online - Keuis Hera Susanti; Camelia Sofwan Al-Rasyid; Ahmadi; Taufik Hidayat; Sisi Ade Linda; Muhamad Izazi Nurjaman (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The rapid growth of digital commerce has intensified manipulative practices such as Fake Order (FO), Fake Buyer (FB), and Fake Review (FR), which are used to artificially inflate product reputation and influence market algorithms. These practices generate asymmetric information that misleads consumers and undermines fair competition. Using a qualitative normative approach based on literature review, relevant regulations, and contemporary fiqh perspectives, the analysis identifies FO, FB, and FR as interconnected forms of digital manipulation. From the perspective of Sharia Economic Law, these practices contain elements of tadlis (fraud), bai’ al-najasy (false bidding), and gharar (uncertainty), all of which are strictly prohibited as they distort consent (antaradin) in transactions. The findings highlight that consumer decisions are often shaped by manipulated digital information, leading to defective contractual consent and potential injustice. By framing these practices as a unified ecosystem of digital fraud, the discussion emphasizes the need for adaptive regulatory measures and stronger ethical enforcement within digital marketplaces. Strengthening platform governance, improving verification systems, and promoting awareness of ethical business conduct grounded in maqasid al-shariah are essential to ensure transparency, protect consumers, and maintain integrity in online trade